Incorporating Waste Material in Stone Mastic Asphalt (SMA) Mixtures: A Systematic Literature Review - Christian Hadhinata; Ary Setyawan; Florentina Pramesti (Journal of Rehabilitation in Civil Engineering)
Waste is one of the largest sources of environmental pollution. This situation is also made worse by waste processing which is only disposed away and piled up in open spaces. Therefore, waste handling and processing are crucial to carry out. One way to achieve those is to use waste material into the stone mastic asphalt (SMA) mixture. Based on this, this paper aims to summarize and review the use of waste materials in SMA mixtures. A systematic literature review technique was used in the research with a database obtained from three reputable sources which explained the effect of adding waste material to the SMA mixture. This paper summarizes the preparation method, mixing method, properties, and environmental perspective analysis regarding the addition of waste material to the SMA mixture. There are also recommendations for further research to explore more deeply the environmental and economic impacts of using different types and volumes of waste in the SMA mixture.